Species peculiarities of the lipid composition of some freshwater fish tissues of the Western Podillya - Lyavrin, B. Z.; Kurant, V. Z.; Khomenchuk, V. O.; Hrubinko, V.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
Aspectual features of individual lipids in the tissues of carp, crucian carp, perch, and pike are shown. Changing the ratios of different classes of non-polar lipids is considered as the response of fish to the action of environmental factors.